Loyalitas Konsumen JNE Surabaya: Korelasi antara Marketing Public Relations dan Kualitas Pelayanan - Kurniawan, Krisna; Zulaikha, Zulaikha (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2018)
This research aims to know the influence of marketing public relation and service quality against customer loyalty at PT Tiki Jalur Nugraha Ekakurir (JNE) Surabaya. The variables used in this study i.e. marketing public relation, service quality, and customer loyalty. The population used in this study are all the consumers who use the service delivery on PT Tiki Jalur Nugraha Ekakurir (JNE) Surabaya.As for the sampling technique used was purposive sampling technique with the total sample as many as 140 respondents. In this research analysis technique used was multiple linear regression analysis. The test results showed that the variables consist of marketing public relation, service quality effect significantly to consumer loyalty on the PT Tiki Jalur Nugraha Ekakurir (JNE) Surabaya. These results indicate that the variable quality of service had a dominant influence on consumer loyalty against PT Tiki Jalur Nugraha Ekakurir (JNE) Surabaya.Â Keywords: marketing public relation, service quality, consumer loyalty